ABNORMALITAS INTERPRETASI ELEKTROKARDIOGRAM MENURUT GAMBARAN NEUROIMAGING PADA STROKE HEMORAGIK - Dedi Sutia* Syarif Indra* Hendra Permana* Andi Fadilah Yusran Putri,* Ribka Ankashima Sembiring* (NEURONA, 2020)
INTODUCTION STROKE IS THE THIRD LEADING CAUSE OF DEATH IN THE WORLD ABOUT 30 OF CASES OF STROKE ARE HEMORRHAGIC CARDIOVASCULAR DISEASE HAS CORRELATION TO STROKE AS RISK FACTOR AND COMPLICATION LEADING TO MORTALITY